2012
DOI: 10.1109/tvcg.2012.274
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Visualization at the Terascale on Desktop PCs

Abstract: Fig. 1. Visualizations of structures in 1024 3 turbulence data sets on 1024 × 1024 viewports, directly from the turbulent motion field. Left: Close-up of iso-surfaces of the ∆ Chong invariant with direct volume rendering of vorticity direction inside the vortex tubes. Middle: Direct volume rendering of color-coded vorticity direction. Right: Close-up of direct volume rendering of R S . The visualizations are generated by our system in less than 5 seconds on a desktop PC equipped with 12 GB of main memory and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The DCT coefficients are nonsymmetrically truncated and then quantized as in the method we exposed for the tensor case. The WT coefficients are compressed with a standard scalar quantization scheme as used in [25]: a quantization step h that determines the overall resulting compression rate is defined for the first wavelet level, and reduced to h/2 l for any other level l as average coefficient energy tends to decrease in subsequent levels. The quantization function is f (x) = sign(x) · round(|x|/h).…”
Section: Resultsmentioning
confidence: 99%
“…The DCT coefficients are nonsymmetrically truncated and then quantized as in the method we exposed for the tensor case. The WT coefficients are compressed with a standard scalar quantization scheme as used in [25]: a quantization step h that determines the overall resulting compression rate is defined for the first wavelet level, and reduced to h/2 l for any other level l as average coefficient energy tends to decrease in subsequent levels. The quantization function is f (x) = sign(x) · round(|x|/h).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in (Treib et al, 2012) a lossy GPU compression scheme for vector data was shown to operate significantly above disk speed. The scheme is based on the discrete wavelet transform, followed by a quantization of wavelet coefficients and a final entropy coding of quantized coefficients.…”
Section: Turbulent Vector Field Compressionmentioning
confidence: 99%
“…The recent survey by (Balsa Rodriguez et al, 2013) provides a more focused treatment of techniques used in the context of volume visualization. Our GPU compression scheme builds upon previous work for performing waveletbased vector field compression including Huffman and run-length decoding entirely on the GPU (Treib et al, 2012).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent survey by Balsa Rodriguez et al [19] provides a focused treatment of compression techniques used in the context of volume visualization. We use the wavelet-based method described by Treib et al [20], [21] for the compression of 3D scalar fields, which decodes the data directly on the GPU from a Huffman-encoded wavelet coefficient stream.…”
Section: Volume Renderingmentioning
confidence: 99%